Association between homocysteinemia and mortality in CKD: A propensity-score matched analysis using NHANES-National Death Index. Issue 36 (9th September 2022) - Song, Je Hun; Huh, Hyuk; Bae, Eunjin; Lee, Jeonghwan; Lee, Jung Pyo; Lee, Jong Soo; Kim, Gwang Sil; Yoo, Kyung Don
Abstract : Hyperhomocysteinemia (HHcy) is considered a risk factor for cardiovascular disease (CVD), including chronic kidney disease (CKD). In this study, we investigated the association between levels of serum homocysteine (Hcy) and mortality, inferred from the presence of CKD. Our study included data of 9895 participants from the 1999 to 2016 National Health and Nutrition Examination Surveys (NHANES). Multivariable-adjusted Cox proportional hazard models using propensity-score, were used to examine dose-response associations between Hcy level and mortality. A total of 9895 participants, 1025 (10.3%) participants were diagnosed with CKD. In a multivariate Cox regression analysis including all participants, Hcy level was significantly associated with all-cause mortality in the nonCKD group, compared to the 1 st quartile in the fully adjusted model (2 nd quartile: hazard ratio (HR) 1.75, 95% confidence interval (CI) 1.348–2.274, P  < .001; 3 rd quartile: HR 2.22, 95% CI 1.726–2.855, P  < .001; 4 th quartile: HR 3.77, 95% CI 2.952–4.830, P  < .001). However, this finding was not observed in the CKD group. The observed pattern was similar after propensity score matching. In the nonCKD group, overall mortality increased in proportion to Hcy concentration (2 nd quartile: HR 2.19, 95% CI 1.299–3.709, P  = .003; 3 rd quartile: HR 2.60, 95% CI 1.570–4.332, P  < .001; 4 th quartile: HR 3.72, 95% CI 2.254–6.139, P  < .001). However, the risk of all-cause mortality according to the quartile of Hcy level, did not increase in the CKD group. This study found a correlation between the Hcy level and mortality rate only in the nonCKD group. These altered risk factor patterns may be attributed to protein-energy wasting or chronic inflammation status, that is accompanied by CKD.